Personal Spiritual-Moral Qualities and Empathy as Components of Higher Moral Capacities: Verification of the Relationship based on a Russian Sample - Galina V. Ozhiganova (Peoples' Friendship University of Russia (RUDN University), 2020)
For contemporary societies, psychological research on moral behaviour, moral manifestations and personality traits has acquired special relevance. In addition, the recent rise of positive psychology offers an important perspective on the study of spiritual-moral qualities (virtues), demonstrating the degree to which a persons happiness in life relates to high spiritual-moral guidelines. Various aspects of personal spirituality, morality and empathy are actively being studied by international scientists; however, in Russian psychology, studies on this topic are scarce. Utilizing a Russian sample, such a study, including the context of higher moral capacities, was conducted for the first time. The theoretical part of this article addresses the issues related to the higher moral capacities, providing definitions and indicating difference between moral capacities and moral abilities: higher moral capacities appropriately belong to the category of spiritual capacities. As part of higher moral capacities, the following components are distinguished: spiritual-moral qualities as a manifestation of a spiritual altruistic orientation and empathy as a manifestation of moral feelings associated with decentration, empathic feeling and empathic care. The relationship between these components is analysed in the empirical part of the article. The purpose of the study was to examine the relationship between indicators of personal spiritual-moral qualities and empathy. The data for the study were collected and processed using The Spiritual Personality Inventory by A. Husain, M. Anas (adapted by G.V. Ozhiganova) and The Interpersonal Reactivity Index by M. Davis (adapted by N.A. Budagovskaya, S.V. Dubrovskaya and T.D. Karyagina). The empirical study involved 90 high school students (girls represented 56% of the sample). The results confirmed our hypothesis: a correlation analysis revealed a relationship between indicators of personal spiritual-moral qualities and empathy in three aspects: (1) cognitive (the Decentration scale), (2) affective (the Empathic Feeling scale) and (3) behavioural (the Empathic Care scale). No relationship was found with the Personal Distress scale reflecting non-spiritual, egocentric tendencies. These findings allow us to consider spiritual-moral qualities (related to a spiritual altruistic orientation) and empathy (disclosed as decentration, empathic feeling and empathic care) as components of higher moral capacities.